RURAL DEVELOPMENT STRATEGIES THROUGH BANGGA MBANGUN DESA POLICY (a Study in Cimrutu Village Cilacap Regency) - Lestari, Sri - (Advances in Social Sciences Research Journal, 2018)
Village is a benchmark point of national development, both physical development and the whole human development. It also prevails for regional government of Cilacap Regency in order to regional development that is conducted through Bangga Mbangun Desa (proud to build the village) policy where regional development starts from the villages. The existence of Cimrutu Village, which is the youngest village in Patimuan Sub-district Cilacap Regency, makes the regional government of Cilacap Regency to be more sensitive in preparing rural development strategies since, in reality, the villagers of Cimrutu Village just felt the development in 2016-2017. The study was conducted to find out the rural development strategies through Regent Regulation No. 76/2011 on Bangga Mbangun Desa. The strategy had been implemented since 2011 but the basic development in the village was felt by the villagers only in early 2017. Through Bangga Mbangun Desa policy, the research aimed to analyze rural development strategies of Cimrutu Village that impacted the rural community self-reliance and gave stimulants to facilitate the community to be independent. Methodology used was descriptive with qualitative approach. Data collection methods used were observation, interview, and documentation. The research result indicates that rural development village in Cimrutu Village had a very slow development direction. First, regarding education pillar, villagers of Cimrutu Village had low awareness on the importance of education. It was proven by the small amount of the villagers aged 18-30 who completed secondary level education (senior high school). Second, regarding economic pillar, there was less competitiveness in local economic products and less optimal of agricultural infrastructures and facilities for the villagers. Third, regarding health pillar, it had directed to a better percentage in national health level due to the adequate health facility level and the low maternal and children mortality. However, in terms of clean water availability, the management was less optimal. Fourth, regarding socio-cultural environmental pillar, there were many infrastructures that were in bad condition either district roads or villager roads. Keywords: Rural Development Strategies, Bangga Mbangun Desa Policy, Community